General time-dependent bounded perturbation of a strongly continuous semigroup - Kartashov, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We consider an evolution family whose generator is formed by a time-dependent bounded perturbation of a strongly continuous semigroup. We do not use the condition of the continuity of a perturbation. We prove a formula for a variation of a parameter and the corresponding generalization of the Dyson-Phillips theorem.